Characterization of the complete mitochondrial genome of the Pohlia nutans M211 from Antarctica. Issue 3 (2nd July 2020) - Cao, Junhan; Yang, Xihong; Wang, Yanfeng; He, Yingying; Qu, Changfeng; Miao, Jinlai
Abstract: The complete mitochondrial genome of Pohlia nutans M211, sequenced using Illumina NovaSeq PE150, was 99864 bp in length. It encoded 65 genes, comprising 38 protein-coding genes, 24 tRNA genes and 3 ribosomal RNA genes. For these 38 PCGs, the most common start codon was ATG and the most common termination codon was TAA. The total GC content was 36.91% while the composition of A + T was 60.39%. Phylogenomic analysis indicated that P. nutans M211 was closely related to Mielichhoferia elongate .